Pengaruh Disiplin Kerja, Kepuasan Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan - Abas, Erjati; Basir, Badirun; Soegiarto, Ita; Kamal, Fahmi; Sofyan, Iradat Rayhan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to reveal the influence of work discipline, job satisfaction and work motivation on employee performance. This research uses a population including employees who are actively working. It is hoped that this research can provide input to companies in managing employee performance, especially related to work discipline, job satisfaction and work motivation. The sample obtained was 80 respondents. The independent variables in this research are work discipline, job satisfaction and work motivation, while the dependent variable is employee performance. In this research, the instrument used was a set of questionnaires with likert scale which were then processed using the IBM SPSS version 26 application software. Analyzing the data that had been collected, used multiple linear regression. The partial research results show that there is a significant influence of work discipline, job satisfaction and work motivation positively on employee performance. Simultaneously, the results of research testing show that work discipline, job satisfaction and work motivation have a significant positive effect on employee performance.